Исследование динамического поведения и напряженно-деформированного состояния в элементах выбивной машины при динамических быстроизменяющихся процессах - Грабовский, Андрей Владимирович; Барчан, Евгений Николаевич (Национальный технический университет "Харьковский политехнический институт", 2008)
У статті наведені результати дослідження виходу вибивної машини на робочий режим. Робочий режим конструкції є зарезонансним, тому при розгоні і зупинці машина повинна перейти через збуджувальну резонансну частоту. Також приведені результати дослідження для фрагментів вибивної машини на перехідний динамічний аналіз при повному циклі навантаження.

In the article the results output of research knock-out machine are presented on an operating condition. An operating condition of construction is above resonance, therefore the machine must pass through resonance forcing frequency at an acceleration and stop. The results of research for knock-out machine’s fragments are also presented on transitional dynamic analysis at the complete cycle of loading.
Keywords: резонансные трансляционные режимы; цикл нагружения; уравнения Лагранжа; сила демпфирования